Novel and efficient method for the reconstruction of adenoviruses through isothermal assembly and its potential applications - Wen, Ke; Resch, Matthew D.; Mazboudi, Ryan; Mulhall Maasz, Hannah; Galarza, Jose M. (Frontiers in Medical Technology, 2023)
Here we describe a novel approach for the genetic engineering of any portion of the adenovirus genome and the reconstruction of either fully replication competent or defective virions. This innovative strategy is rapid, effective and suitable for the manipulation of the entire genome broadening the spectrum of potential applications for the adenovirus system. Our strategy involved insertion of restriction enzyme recognition sequences absent in the native virus into the termini of the adenovirus genome in order to facilitate recovery. These restriction enzyme sites, together with the two inverted terminal repeats and packaging sequences, were synthesized and then subcloned into the pBR322 vector. The remaining internal portion of the adenovirus genome was separated and amplified via PCR into six segments, of which groups of two were joined together by PCR and then subcloned into pBR322 plasmids. During the PCR reaction, an overlap of 30 to 40 bp was added to the termini of the adjacent fragments, allowing for the subsequent isothermal assembly and correct orientation of all fragments. This approach allows for the genetic modification of each genomic fragment according to the specific research goals, (e.g.: deletion, substitution, addition, etc.) To recreate the entire viral genome, the four engineered fragments (each comprised of two adenovirus genomic sections) as well as the pBR322 backbone, were reassembled into a single construct utilizing an isothermal assembly reaction. Finally, the reassembled plasmid containing the entire genome was linearized and transfected into HEK293 cells to recover the complete reconstructed adenoviral vector. Using this approach, we have successfully generated two recombinant reporter adenoviruses, one of human adenovirus serotype 14 and another of serotype 55. The E3 region was replaced by the reporter genes (GFP and Luciferase) to visualize and track the recovery process. Subsequent infection of A549 cells with these reconstructed adenovirus vectors demonstrated that they were replication competent. This method shortens the viral reconstruction process because the one-step isothermal assembly requires less than 4 days, and recombinant adenovirus recovery occurs within 10 days. This new method can be used to construct or manipulate any adenovirus whose complete genome sequence is known.